The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su12010164
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Environmental Values and Attitudes of Rural Nepalese Children by Validating the 2-MEV Model

Abstract: The Two-dimensional Model of Ecological Values (2-MEV), developed and verified in Western Europe, successfully explores the environmental values and attitudes of the children (11−16 years old) using questionnaires/items. However, the reliability of the 2-MEV Scale and its bi-dimensionality in a non-industrialised country, such as Nepal, is unexplored. Nepal lies within the monsoon region, which triggers extreme environmental crises such as floods. As environmental values and attitudes are related to pro-enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Throughout its long history, the 2-MEV has undergone modifications, adaptations, and shortenings. Even shorter versions of the 2-MEV without PRE 6 have already been applied and confirmed successfully in recent studies [60,64]. Schönfelder and Bogner [46] used and validated an 11-item version without PRE 3 and could report the expected 2-factor-structure.…”
Section: Environmental Values Of the Primary School Samplementioning
confidence: 80%
See 1 more Smart Citation
“…Throughout its long history, the 2-MEV has undergone modifications, adaptations, and shortenings. Even shorter versions of the 2-MEV without PRE 6 have already been applied and confirmed successfully in recent studies [60,64]. Schönfelder and Bogner [46] used and validated an 11-item version without PRE 3 and could report the expected 2-factor-structure.…”
Section: Environmental Values Of the Primary School Samplementioning
confidence: 80%
“…Developed in the 1990s, the 2-MEV has been repeatedly used in different contexts and within various populations during the past decades. Bi-national investigations, e.g., [47,54,55], internal cross-validation studies, e.g., [56], and, even more importantly, independent research groups, e.g., [57][58][59][60][61], have repeatedly used the instrument and have confirmed its validity and reliability. Within the past decades, the 2-MEV has been continuously developed and improved.…”
Section: The Relationship Between Cognitive Achievement and Environme...mentioning
confidence: 99%
“…While at that time many scales were competing, the 2-MEV received the privilege of independent cross-cultural confirmation from different disciplines (e.g., [5,10,[16][17][18]). Subsequently, the model has been used around the globe and translated into 33 languages, the very basis for its consistency being those bi-national studies; recently, e.g., Regmi et al [19] applied the 2-MEV with 200 rural Nepalese students and confirmed its validity and reliability. The instrument's worldwide acceptance is rooted in its compact format and two-dimensionality, which covers preservation of nature (a biocentric perspective to protect our natural environment) and utilization of nature (an anthropocentric perspective to exploit nature) [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding the differences between cultures was beyond the scope of the study. There is evidence of cultural differences in ecological values; for example, in a Nepalese sample, Regmi, Johnson and Dahal [67] replicated the original finding that preservation and utilisation are separable aspects of environmental values [65], but not that they are orthogonal. While we attempted to create a generalisable theory, arguably none of the segments recruited for our study represented a general population sample.…”
Section: Limitationsmentioning
confidence: 89%